Hopping to conclusions: using anuran mating decisions to study temporal integration over prolonged timescales - Alayoubi, Amir Khaled, author; Hoke, Kim, advisor; Davies, Patricia, committee member; Williams, Cory, committee member; Myers, Brent, committee member (Colorado State University. Libraries, 2026)
Temporal integration is a perceptual process where the brain sequentially accumulates noisy sensory evidence over time to inform a perception or plan of action, and is important for acoustic communication in humans and other species where communication involves a sequential series of signals. Studying temporal integration has been traditionally limited to highly controlled environments and tasks lasting two seconds or less, and is in need of more external inquiry into ethologically relevant scenarios. Here, the diploid gray treefrog, Hyla chrysoscelis, was leveraged to investigate the perception of repetition intervals over time because females naturally show mating preferences for regular and faster signal repetition, a trait that requires temporal integration for ten seconds or longer. A custom-built enclosure with sensitive recording equipment was developed and optimized to measure instantaneous responses to sounds to identify behavioral outputs of temporal integration through female preferences. Despite clear preferences for a signal series amongst other alternatives, the responses to all signals within all series were nearly identical in strength and reaction time, but different directionally. The likelihood to respond in the direction of a speaker emerged as a candidate metric for temporal integration, and was sensitive to choice complexity. This work offers exciting new avenues and possibilities for future investigations into the neural and cognitive mechanisms of temporal integration over prolonged timescales in ethologically relevant settings, as well as mechanisms that explain perceptual sensitivity to complex signaling environments.
Keywords: decision; integration; timescales; evidence; accumulation; prolonged